Associated Factors of Postpartum Modern Contraceptive Use in Burie District, Amhara Region, Ethiopia - Wassachew Ashebir; Tilahun Tadesse (Journal of Pregnancy)
Introduction. The first 12 months after giving birth in relation to family planning use is the time which is often given less attention by health care managers, health service providers, and users. Even most women do not realize that they are at risk for subsequent pregnancy. Due to this, there is an increased substantial risk of unwanted conception and an often-frustrated desire for contraceptive protection. As a result, many women in the postpartum period did not start use of any modern contraceptive method. Therefore, the objective of this study was to assess associated factors of postpartum modern contraceptive use in Burie District, Amhara Region, Ethiopia. Methods. A community-based cross-sectional study was employed among 686 mothers in Burie District from March 16 to March 25, 2017. A multistage sampling technique was used to select the study participants. Data were collected using face to face interviewer administered structured questionnaires. Then, the collected data was entered, coded, and cleaned into EPI Data version 3.1 and exported to SPSS version 20.0 for data analysis. Bivariate and multivariate logistic regression was done to assess the association of factors with postpartum modern contraceptive use. Adjusted odds ratios with 95% confidence intervals were calculated, and p values <0.05 were considered to indicate statistical significance. Result. This study revealed that postpartum modern contraceptive use was found to be 20.7%. Postpartum modern contraceptive use was significantly associated with women’s level of education (AOR=0.15, 95% CI (0.03-0.71)), discussing FP methods with partner (AOR=0.60, 95% CI (0.40-0.90)), knowing menses return after birth (AOR=0.39, 95% CI (0.25-0.59)), ever heard about modern FP methods (AOR=0.06, 95% CI (0.01-0.43)), and contacting health professionals (AOR=1.85, 95% CI (1.19-2.88)). Conclusion and Recommendations. Postpartum modern contraceptive use was found to be low. Therefore, health professionals should work on improvements in women’s educational status, making awareness of the women and counseling of their husbands about the use of postpartum contraception, when fertility returned and risky timing for becoming pregnant.